Analisis Tindak Tutur Netizen pada Kolom Komentar Instagram @persibrebels: Studi Kualitatif terhadap Konten Resbob - Novita Abelia Tisnawati; Nantia Rena Dewi Munggaran; Dudi Yudhakusuma (GLOBAL SCIENTS PUBLISHER, 2026)
Social media has evolved into a digital communication platform that allows people to share their criticisms, assessments, and opinions on various issues being discussed, one of which occurs through the Instagram comment section. This study aims to identify the forms of netizens' speech acts, analyze the communicative meaning contained in netizens' comments, and explain the tendency of dominant speech act types reflected in the comment interactions on Resbob's content uploaded by the Instagram account @persibrebels. This study uses a qualitative method with a qualitative content analysis approach. The research data consisted of 55 netizen comments collected through observation and documentation techniques, then analyzed using John L. Austin's speech act theory covering locutionary, illocutionary, and perlocutionary acts, with illocutionary classification referring to Searle's categories. The results show that locutionary acts are dominated by comments containing calls to action (24 data) as well as assessments and condemnations of the perpetrator (23 data). The most dominant illocutionary acts are directive (26 data) and expressive (16 data), shown through calls to report, demands against the perpetrator, and expressions of anger and disappointment. Meanwhile, perlocutionary acts show that netizens' comments most often encourage account-reporting actions (17 data) and trigger collective condemnation (15 data), besides building group solidarity and raising legal awareness. These findings indicate that the Instagram comment section functions not only as a means of expressing opinions but also as a digital communication space that allows netizens to shape meaning, express emotions, and influence public responses to issues deemed sensitive.